Peutz-Jeghers syndrome in a woman presenting as intussusception: A case report. (February 2021) - Syarifuddin, Erwin; Masadah, Rina; Lusikooy, Ronald Erasio; Warsinggih,; Uwuratuw, Julianus Aboyaman; Faruk, Muhammad
Highlights: Peutz-Jeghers syndrome (PJS) is an inherited polyposis syndrome. PJS-characteristic hamartoma polyps occur in the gastrointestinal (GI) tract. In patients with intussusception, the presence of a hamartoma polyp may have been the trigger. Hamartoma polyps in the GI mucosa and hyperdense macular lesions on the lip and buccal mucosa are pathognomonic signs of PJS. Abstract: Introduction: Peutz-Jeghers syndrome (PJS) is an uncommon autosomal dominant syndrome with a variable to high penetrance that leads to the development of polyps within the gastrointestinal mucosa. Here we report a case of an adult female suffering jejunoileal intussusception due to PJS. Presentation of case: A 30-year-old woman came to an emergency department with a small bowel obstruction caused by intussusception. The patient underwent an emergency exploratory laparotomy. An intussusception at the level of 60 cm from the ligamentum treitz was revealed, and the intussusception small bowel segment was not viable; we decided to perform segmental jejunoileal resection with the Bishop-Koop procedure, and the specimen histopathology of the segmental jejunoileal resection showed a typical hamartomatous polyp features. Two month later, diagnostic endoscopy showed multiple polyps (between 5 and 15 mm) in the large bowel. The polyps were removed with endoscopic polypectomy and examined histopathologically, showing characteristics of PJS. Further detailed family history was obtained, and similar skin lesions were detected on our patient's child (since birth). Although endoscopy screening identified multiple polyps in the child's ileum and large bowel, he was not suffering from abdominal symptoms. Conclusion: In patients with intussusception at a young age, PJS can be caused by the presence of a hamartoma polyp as a trigger for intussusception. If there are multiple polyps found in the gastrointestinal mucosa and other pathognomonic signs are found, such as hyperdense macular lesions on the lip and buccal mucosa, such cases should be confirmed as PJS.